Different Electrocatalytic Response Related to the Morphological Structure of TiO2 Nanomaterial: Hydroquinone as an Analytical Probe. Issue 1 (25th October 2016) - Mazloum‐Ardakani, Mohammad; Yavari, Mozhgan; Khoshroo, Alireza
Abstract: Two shapes of TiO2 nanomaterial will largely affect the catalytic activity. TiO2 nanoparticles (NPs) and TiO2 nanofibers (NFs) were used to investigate the effect of shape on catalytic activities and get the optimum shape of catalysis. Electrochemical behaviors of two modified electrodes by TiO2 nanomaterial were evaluated by cyclic voltammetry and electrochemical impedance spectroscopy. Various electrochemical parameters such as electrode surface area and electron‐transfer rate constant were also studied and calculated in the aqueous solution. Results showed that the response of NF is better than NP for electrooxidation of hydroquinone (HQ). The different electrochemical response of TiO2 is related to the various morphological structures, so controlling the shape and structure of nanomaterial is very important factor which is because of the powerful correlation between these parameters and their optical, catalytic and electrical properties. Abstract :